2017
DOI: 10.4236/ojog.2017.713126
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Prognosis of the Hysterectomy Operation in the Obstetrics and Gynecology Department at the University Teaching Hospital of Ouagadougou (UTH-YO), Burkina Faso

Abstract: Objective: To describe the indications and the prognosis of the hysterectomy operation in the obstetrics and gynecology department at the UTH-YO, Ouagadougou, Burkina Faso. Methodology: It has been a descriptive cross-sectional study over a period of 18 months from 1 January 2014 to 30 June 2015 in the obstetrics and gynecology department of the UTH-YO. The variables studied were demographics, clinical and prognostic aspects. Results: During the study period, we recorded 128 cases of hysterectomies including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…10 For instance, participants living in a bungalow or groundfloor of a multistorey building will report less mobility challenges, compared to those living in mansions or higher floors within a multistorey building. The findings of this study match those reported in Indonesia, 11 where 77.0% of females enrolled did not experience any difficulties with mobility, 83.9% were able to perform self-care activities without any problem, and two-thirds (66.7%) performed their usual activities with ease. More than half of the participants enrolled in the Indonesian study 11 experienced moderateto-severe problems in their assessment of pain or discomfort, as well as anxiety or depression.…”
Section: Articlesupporting
confidence: 86%
“…10 For instance, participants living in a bungalow or groundfloor of a multistorey building will report less mobility challenges, compared to those living in mansions or higher floors within a multistorey building. The findings of this study match those reported in Indonesia, 11 where 77.0% of females enrolled did not experience any difficulties with mobility, 83.9% were able to perform self-care activities without any problem, and two-thirds (66.7%) performed their usual activities with ease. More than half of the participants enrolled in the Indonesian study 11 experienced moderateto-severe problems in their assessment of pain or discomfort, as well as anxiety or depression.…”
Section: Articlesupporting
confidence: 86%
“…Obstetric hysterectomy is often performed as an emergency procedure for haemostasis reasons. In gynaecology, the indications are dominated by benign or malignant tumours of the uterus [2,3]. Hysterectomy remains the most frequently performed procedure in gynaecological surgery, whatever the cause, with over 45,000 operations per year worldwide.…”
Section: Introductionmentioning
confidence: 99%